Social psychology of education as a branch of scientific knowledge - М.Е. Sachkova; O.B. Krushelnitskaya; V.А. Orlov (Психологическая наука и образование (2007. Online), 2013)
The article discusses the emergence of a new scientific field – social psychology of education. Most of the key phenomena that contemporary social psychology examines, cannot influence training and education success of an individual. Therefore, in addition to traditional general psychological, psycho-pedagogic, developmental, psychophysical and other approaches solving the problems of the education system; the possibility is considered of increasing the efficiency of the educational process by means of a rapidly growing social psychology. The prospects of this approach is evidenced by the results of numerous Russian and international research, including those performed in Moscow State University of Psychology and Education. The article discusses ways to develop the concept of the social psychology of education, approaches to the definition of its subject, goals and objectives, as well as new methods of the discipline. The possibilities of further use of the potential of social psychology are analyzed to address the efficiency of the educational process and the full personal development of students.